Pengaruh Kepemimpinan Dan Penempatan Terhadap Semangat Kerja Dan Kinerja Pegawai Sekretariat Daerah Kabupaten Rokan Hulu - roni candra; Sri Indarti; Yusni Maulida (Jurnal Economica, 2020)
This study aims to determine the effect of leadership and placement on employee morale and performance of Regional Secretariat of Rokan Hulu Regency. This study aims to determine the effect of leadership and placement on morale and performance of Regional Secretariat of Rokan Hulu Regency. This research is a quantitative descriptive study. The data used in this study are primary data by giving questionnaires to all ASN in the Regional Secretariat of Rokan Hulu Regency and secondary data obtained from several literatures, documents, reports and scientific papers as well as other supporting related to this research. Data analysis method used in this study is path analysis to test hypotheses with the help of SPSS For Windows Version 21 software. The results showed that there was a positive and significant direct effect between leadership on morale, leadership on performance, and morale on employee morale on the performance of the Regional Secretariat. While the placement variable on morale and placement on performance there is a positive but not significant direct effect. The indirect effect of leadership on performance through morale is positive and significant, while the placement variable on performance through morale is positive but not significant.